2017
DOI: 10.1097/md.0000000000008233
|View full text |Cite
|
Sign up to set email alerts
|

Topical use of tranexamic acid can effectively decrease hidden blood loss during posterior lumbar spinal fusion surgery

Abstract: In spinal fusion surgery, total blood loss (TBL) is composed of visible blood loss from the surgical field and wound drainage, and hidden blood loss (HBL). Until now, no published studies exist reporting the effect of topical use of tranexamic acid (tTXA) on HBL in patients undergoing posterior lumbar spinal fusion surgery. This study aimed to explore the effect of tTXA on HBL during primary posterior lumbar spinal fusion surgery. Between September 2014 and September 2016, 100 adult patients (age > 18 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…Xu et al 26 reported that no patient developed adverse reactions attributable to the topical administration of TXA and there were no differences in any of the parameters representing wound problems or readmissions within 30 days from discharge between patients with the topical use of TXA and patients in the control group. Similarly, Ren et al 27 reported that topical use of tranexamic acid can effectively decrease hidden blood loss, without significant complications in adult patients undergoing posterior lumbar spinal fusion surgery. The results of the present study also indicate no statistically significant differences for wound complications between the two cohorts.…”
Section: Discussionmentioning
confidence: 96%
“…Xu et al 26 reported that no patient developed adverse reactions attributable to the topical administration of TXA and there were no differences in any of the parameters representing wound problems or readmissions within 30 days from discharge between patients with the topical use of TXA and patients in the control group. Similarly, Ren et al 27 reported that topical use of tranexamic acid can effectively decrease hidden blood loss, without significant complications in adult patients undergoing posterior lumbar spinal fusion surgery. The results of the present study also indicate no statistically significant differences for wound complications between the two cohorts.…”
Section: Discussionmentioning
confidence: 96%
“…No additional studies were obtained after the reference review. Ultimately, three RCT [ 11 , 15 , 16 ] and one non-RCT [ 12 ] were eligible for data extraction and meta-analysis. The search process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Topical application of TXA would decrease systemic absorption and result in lower risk of adverse reactions. Recently, several studies [ 10 12 ] have reported topical application of TXA in spinal surgery. However, there is still no consensus whether to use topical application of TXA during spinal surgery or not.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated HBL is commonly occurred in the perioperative period of posterior spinal The underlying mechanism for HBL remains elusive. [10][11][12] To our knowledge, there are many reports about the mechanisms of HBL only focusing on joint surgery, but few reports have mentioned spinal surgery. Therefore, we carried out this study to investi- March 2019 CHINESE MEDICAL SCIENCES JOURNAL 42 cells.…”
Section: Discussionmentioning
confidence: 99%